The Contribution of Environmental Diplomacy to Disaster Risk Reduction - Alrehaili, Naif Rashed (International Journal of Disaster Management, 2024)
This study critically examines the contribution of environmental diplomacy in disaster risk reduction (DRR), emphasizing its importance in mitigating the impacts of natural hazards exacerbated by climate change. As global environmental challenges increase, the intersection of international diplomatic efforts and DRR becomes essential for promoting resilience and reducing vulnerabilities. Through a comprehensive analysis of the UNDRR Frameworks, this research investigates how environmental diplomacy contributes to DRR by facilitating international cooperation, enhancing resource allocation, and fostering knowledge dissemination. The study employs an interpretive qualitative inductive methodology, incorporating case studies to identify best practices and challenges in aligning environmental diplomacy with DRR objectives. Findings reveal that robust environmental diplomacy significantly enhances disaster preparedness by promoting cross-border collaboration, accelerating access to climate finance, and integrating local capacities into global frameworks. However, challenges remain, particularly in terms of implementation gaps, accessibility to financial resources, and the representation of vulnerable nations in decision-making processes. Key recommendations include strengthening international diplomatic engagements, streamlining climate finance mechanisms, and promoting regional cooperation to address shared risks. Additionally, the study advocates for integrating DRR into national development policies, enhancing community-based resilience efforts, and improving monitoring and evaluation systems to track DRR progress. The research concludes that by reinforcing the synergies between environmental diplomacy and DRR, the global community can better address the increasing risks posed by climate-related disasters and build more sustainable, resilient societies